Dystocia and its management in a captured wild Monkey - G, Aswini Sivan; Kujur, Anju; Kumar, Brijesh; Srivastava, Neeraj; Sahu, Tarun; MP, Thejaswini; Sharma , Renu (Animal Reproduction Update, 2022)
A stray wild female monkey, aged 5-6 years were presented to the Referral Veterinary Polyclinics, ICAR- Indian Veterinary Research Institute, with a history of straining and discharge from the vulva since morning. A close physical examination of the external genitalia of the monkey revealed it as prominent, red and swollen implying pregnancy. The vulva was open due to the internal pressure revealing foetal part visible with reduced fetal fluid. Per-vaginal examination revealed a foetal head in the birth canal, but absence of foetal responses. Per vaginal examination revealed foetal presentation to be anterior longitudinal, dorso-sacral position, but it was difficult to palpate postural condition. To relieve the condition female monkey was positioned in a left lateral recumbent position followed by ample lubrication of the birth canal with CMC (Carboxymethyl cellulose) gel using an intrauterine catheter and syringe. The traction approach was used to extract the dead foetus. Following successful delivery bleeding was prevented by administering ethamsylate injections at a dose rate of 15 mg/Kg (1 ml), and other supportive medications were administered. The macaque monkeys can postpone labour making it difficult for an observer to determine the indicators of dystocia until the condition has worsened. This makes dystocia in nonhuman primates a grave condition requiring prompt medical attention.
Keywords: Dystocia; Monkey; wild animal; management